2014
DOI: 10.1073/pnas.1315466111
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative gustatory inputs affect Drosophila lifespan partly in parallel to dFOXO signaling

Abstract: In Caenorhabditis elegans, a subset of gustatory neurons, as well as olfactory neurons, shortens lifespan, whereas a different subset of gustatory neurons lengthens it. Recently, the lifespan-shortening effect of olfactory neurons has been reported to be conserved in Drosophila. Here we show that the Drosophila gustatory system also affects lifespan in a bidirectional manner. We find that taste inputs shorten lifespan through inhibition of the insulin pathway effector dFOXO, whereas other taste inputs lengthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…Previous work has provided compelling evidence that nutrientsensing signaling pathways are key regulators of longevity (10,43). Additionally, there is a conserved role for the function of chemosensory systems in control of aging (1,5,6,44,45), including a study in PNAS showing that subsets of gustatory inputs were capable of modulating Drosophila lifespan in a bidirectional manner (6). One logical prediction followed that, in response to transduction and integration of a taste signal, an organism reprograms its metabolic state through modulation of nutrient homeostatic pathways, ultimately altering lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has provided compelling evidence that nutrientsensing signaling pathways are key regulators of longevity (10,43). Additionally, there is a conserved role for the function of chemosensory systems in control of aging (1,5,6,44,45), including a study in PNAS showing that subsets of gustatory inputs were capable of modulating Drosophila lifespan in a bidirectional manner (6). One logical prediction followed that, in response to transduction and integration of a taste signal, an organism reprograms its metabolic state through modulation of nutrient homeostatic pathways, ultimately altering lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory systems that detect environmental stimulus mediate at least part of this influence on lifespan. In the nematode C. elegans, as well as in D. melanogaster, the removal of sensory neurons can modulate the lifespan of the organism (Apfeld & Kenyon, 1999; Alcedo & Kenyon, 2004; Libert et al ., 2007; Poon et al ., 2010; Ostojic et al ., 2014). Recent work has also shown that sensory signaling can also modulate the lifespan of vertebrates (Riera et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Gustatory and olfactory neurons, which perceive chemical signals, are some of the sensory neurons that have been shown to affect life span (Alcedo and Kenyon 2004;Libert et al 2007;Poon et al 2010;Ostojic et al 2014;Waterson et al 2014). In C. elegans, chemosensory neuronal signaling is initiated by the binding of chemical ligands to sensory G protein-coupled receptors (GPCRs), which in turn activates G protein signaling cascades to transduce the signals that increase cyclic GMP (cGMP) levels (Bargmann 2006).…”
mentioning
confidence: 99%